Heat Flux estimation in WEST divertor with embedded thermocouples. Issue 3 (September 2016) - Gaspar, J.; Corre, Y.; Firdaouss, M.; Gardarein, J-L.; Guilhem, D.; Houry, M.; Niliot, C. Le; Missirlian, M.; Pocheau, C.; Rigollet, F.
Abstract: The present paper deals with the surface heat flux estimation with embedded thermocouples (TC) in a Plasma Facing Component (PFC) of the WEST Tokamak. A 2D nonlinear unsteady calculation combined with the Conjugate Gradient Method (CGM) and the adjoint state is achieved in order to estimate the time evolution of the heat flux amplitude and decay length λq . The method is applied on different synthetic measurements in order to evaluate the accuracy of the method. The synthetic measurements are generated with realistic values of λq and magnitudes as those expected for ITER.